Strategic Planning of Information Systems and Technology Using the Ward and Peppard Method at Politeknik Internasional Bali - Dana, I Made Kresna; Sariyasa, Sariyasa; Sunarya, I Made Gede (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
This study aims to formulate a strategic plan for the Information System (IS) and Information Technology (IT) at Politeknik Internasional Bali with the objective of enhancing the performance of business processes. The research employs a methodology that includes Ward and Peppard analysis, SWOT analysis, PEST analysis, Porter's Five Forces analysis, and Value Chain analysis. This comprehensive approach evaluates both the external and internal environments of the company, including the SI/TI company environment. The research provides strategic recommendations for the development of IS business strategies, IT strategies, and SI/TI management at Politeknik Internasional Bali. The findings from the SWOT Matrix Analysis reveal that Politeknik Internasional Bali is situated at coordinates (0.63, 1.74), indicating a strategic emphasis on SO (Strength-Opportunity) strategies. The suggested recommendations stemming from this analysis involve the design of information systems that actively support business processes, with a priority on systems located in the Strategic quadrant. The proposed IT Business strategies recommend the design of IT infrastructure architecture based on best practice principles, encompassing elements such as Availability, Scalability, Security, Serviceability, and Manageability. In addition to these recommendations, there is a proposal for organizational structural changes within Politeknik Internasional Bali, including the establishment of a dedicated SI/TI division to reinforce SI/TI management strategies. Overall, these recommendations are geared towards enhancing the overall effectiveness and efficiency of SI/TI utilization at Politeknik Internasional Bali.